Comments on recent achievements of research on dense magnetized plasmas in Poland - Sadowski, M.J. (Вопросы атомной науки и техники, 2018)
This invited lecture presents author’s comments on results of the experimental studies of dense and high-temperature
plasmas, which were carried out in Poland during recent two years. Those studies were performed with the PF-360U
device at NCBJ, and the PF-1000U facility at IFPiLM. There were investigated fast electron beams and soft x-rays, an
influence of thin metal wires and/or an admixture of heavier gases, an influence of a shape of the anode end, as well as
plasma micro-structures in a pinch column, i.e. plasma filaments and hot-spots (of electron densities > 10¹⁹ cm⁻³
and
electron temperatures ranging several keV). The detailed studies concerned also the VR and x-ray emissions, estimates of
local electron temperatures, and fast deuteron beams. Other experiments were devoted to investigation of plasma jets
which can have dimensionless parameters corresponding to astrophysical objects. There are also presented some examples
of the technological applications of PF discharges, studied in a frame of the Polish-Ukrainian scientific collaboration. The
author’s comments are followed by proposals of some future theoretical and experimental studies. Представлено коментарі автора про результати експериментальних досліджень щільних і
високотемпературних плазм, що проводилися в Польщі протягом останніх двох років. Ці дослідження
проводилися на установках ПФ-360U у Національному центрі ядерних досліджень та ПФ-1000U в Інституті
фізики плазми і лазерного мікросинтезу. Особливу увагу приділено вивченню швидких електронних пучків і
рентгенівського випромінювання, впливу тонких металевих дротів і/або суміші важких газів, впливу форми
анода, а також плазмових мікроструктур у пінчі, тобто плазмових ниток і гарячих точок з електронною
густиною > 10¹⁹ см⁻³
і електронними температурами близько декількох кілоелектронвольт. Детально описано
також дослідження видимого та рентгенівського випромінювань, оцінки локальних електронних температур
і пучків швидких дейтронів. Інші експерименти були присвячені вивченню плазмових струменів, які мають
розміри, що відповідають астрофізичним об'єктам. У рамках польсько-українського наукового
співробітництва представлені деякі приклади технологічного застосування ПФ-розрядів.
Автор пропонує деякі теоретичні та експериментальні ідеї для подальших досліджень у цій області. Представлены комментарии автора о результатах экспериментальных исследований плотных и
высокотемпературных плазм, которые проводились в Польше в течение последних двух лет. Эти
исследования проводились на установках ПФ-360U в Национальном центре ядерных исследований и ПФ1000U в Институте физики плазмы и лазерного микросинтеза. Особое внимание уделялось изучению
быстрых электронных пучков и рентгеновского излучения, влияния тонких металлических проволок и/или
смеси тяжелых газов, влияния формы анода, а также плазменных микроструктур в пинче, т.е. плазменных
нитей и горячих точек с электронной плотностью > 10¹⁹ см⁻³ и электронными температурами порядка
нескольких килоэлектронвольт. Детально описано также исследование видимого и рентгеновского
излучений, оценки локальных электронных температур и пучков быстрых дейтронов. Другие эксперименты
были посвящены изучению плазменных струй, которые имеют размеры соответствующие астрофизическим
объектам. В рамках польско-украинского научного сотрудничества представлены некоторые примеры
технологического применения ПФ-разрядов. Автор предлагает некоторые теоретические и
экспериментальные идеи для последующих исследований в этой области.